1969
DOI: 10.1111/j.1464-410x.1969.tb09919.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Studies of Calcium Oxalate in the Presence of Various Ions and Compounds

Abstract: CALCIUM oxalate is important biologically because it is a major constituent of urinary calculi. Both calcium oxalate 1 HzO (whewellite) and calcium oxalate 2 to 23 HzO (weddellite) have been identified, but analyses of collections of stones have shown that the overall amount of whewellite present generally exceeds that of weddellite. Another form of hydrated calcium oxalate, usually referred to as the trihydrate, has been found in only one calculus (Prien, 1963). We have shown (Su1 or, unpublished work) that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 8 publications
1
38
0
Order By: Relevance
“…The formation of these crystals and the effect of various substances on their growth rate have also been studied [11][12][13]. In some studies, Zn was demonstrated to be an effective inhibitor on crystal formation in urine [12,13]. Nevertheless, the results for Zn may be deceptive because of the fact that the inhibitory effect of Zn is shown at relatively high concentrations in buffer solution or in urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these crystals and the effect of various substances on their growth rate have also been studied [11][12][13]. In some studies, Zn was demonstrated to be an effective inhibitor on crystal formation in urine [12,13]. Nevertheless, the results for Zn may be deceptive because of the fact that the inhibitory effect of Zn is shown at relatively high concentrations in buffer solution or in urine.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies showing that calcium oxalate crystals, one of the most common constituents of renal calculi, are easily produced in in vitro trials. The formation of these crystals and the effect of various substances on their growth rate have also been studied [11][12][13]. In some studies, Zn was demonstrated to be an effective inhibitor on crystal formation in urine [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…We then supposed that the determination of lead, cadmium, nickel, and aluminum contents of inner nucleus and outer crust parts of various kinds of urinary calculi might give useful information to reach a decision on whether some trace elements, including essential and toxic ones, play a part in the disease or not. Suggestions that some trace elements tend to enhance the growth rate of deposits of crystalline calcium compounds and thus may play a part in influencing, causing, accelerating, or inhibiting the precipiation of urinary tract calculi [7][8][9] make the elucidation of these and other related subjects significant.…”
Section: Introductionmentioning
confidence: 99%
“…The role of heavy metals in kidney stone formation is not well established. Some of these heavy metals may have an effect on the initial crystallization of stone components, while others affect crystal aggregation and stone growth [14,15,16]. Zinc accounts for the majority of the heavy metals in calcium-based kidney stones [5], and is present in both stone nucleus and the crust [17].…”
Section: Discussionmentioning
confidence: 99%